Modeling water balance components and irrigation efficiencies in relation to water requirements for double-cropping systems - Ali, Md. Hazrat; Lee, Teang Shui; Kwok, Chee Yan; Eloubaidy, Aziz F.; Foong, K.C. (Elsevier, 2000)
This paper describes the estimation of total water requirements as well as reservoir releases required to replenish the water deficit for double cropping of rice. A water balance equation is derived and the performance of a project is analyzed. The water balance components were modeled without calibration, and compared with measured data whenever possible. The potential evapotranspiration ETp were modeled for monthly time series using Penman–Monteith model [Monteith, J.L.,1965. Symp. Soc. Exp. Biol. 19, 205–234]. To estimate surface runoff, the proportion of elementary areas that are saturated were described by a spatial distribution function, considering the average total existing water (TEW) of both cropping seasons from 1991 to 1997. The monthly rainfalls (1971–1997) of 53 uniformly distributed rainfall stations were averaged and the rainfall considered uniform over the whole area. The effective meteorological input Me was considered positive to produce runoff. The variation of the soil suction head and hydraulic conductivity with moisture content, studied by Brooks and Corey [Brooks, R.H., Corey, A.T., 1964. Hydraulic properties of porous media. Hydrology Paper No. 3, Colorado State University, Fort Collins, CO] was applied in the Green–Ampt model [Green, W.H., Ampt, G.A., 1911. J. Agric. Sci. 4 (1), 1–24] to estimate infiltration.